2009
DOI: 10.1038/bmt.2008.429
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation for relapsed non-Hodgkin's lymphoma using intravenous busulfan and cyclophosphamide as conditioning regimen: a single center experience

Abstract: High-dose chemotherapy with autologous SCT has become standard of care for patients with relapsed aggressive non-Hodgkin's lymphoma (NHL). To improve safety and efficacy of this treatment, new conditioning regimens are being developed. We retrospectively reviewed clinical data of patients with relapsed NHL treated at our institution with i.v. BU and CY (BU/CY) as conditioning regimen for autologous SCT between January 2000 and April 2005. We identified 43 patients (24 men, 19 women, median age 50) with diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…This is further confirmed by a TRM of 2.4%, which compares favorably with that reported for similar carmustine-based regimens (0 to 11%) and other types of high-dose conditioning (0 to 25%), with variations being mostly related to patient age and/or comorbidity status. [1][2][3][4]22,[28][29][30][40][41][42] Regarding the acute toxicity of FEAM, we observed a relatively high incidence of mucositis, which was, however, equal or higher than G3 severity in only 30% of episodes. Although the design of this study did not foresee comparison with standard BEAM, it is noteworthy that a recent investigation reported that 83% of patients receiving BEAM experienced oral mucositis, which was graded G1/G2 in 42% of cases and G3/G4 in the remaining 41% of patients.…”
Section: Discussionmentioning
confidence: 84%
“…This is further confirmed by a TRM of 2.4%, which compares favorably with that reported for similar carmustine-based regimens (0 to 11%) and other types of high-dose conditioning (0 to 25%), with variations being mostly related to patient age and/or comorbidity status. [1][2][3][4]22,[28][29][30][40][41][42] Regarding the acute toxicity of FEAM, we observed a relatively high incidence of mucositis, which was, however, equal or higher than G3 severity in only 30% of episodes. Although the design of this study did not foresee comparison with standard BEAM, it is noteworthy that a recent investigation reported that 83% of patients receiving BEAM experienced oral mucositis, which was graded G1/G2 in 42% of cases and G3/G4 in the remaining 41% of patients.…”
Section: Discussionmentioning
confidence: 84%
“…30,31 The data presented here suggest that the fraction of patients that have a lessthan-optimal first collection is substantial: 30% in multiple myeloma, 71% in non-Hodgkin lymphoma, and 57% in Hodgkin disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other efficient alternatives to BEAM are busulfan and cyclophosphamide with or without etoposide. [27][28][29][30] In a recent large registry study with 4917 patients with lymphoma, outcomes of various commonly used high-dose regimens (BEAM, cyclophosphamide/ carmustine/etoposide, busulfan/cyclophosphamide, TBI-based), several significant but often only subtle outcome differences between different HDT platforms were found in individual non-Hodgkin lymphoma subsets. 31 Similarly, slight differences may exist between the comparators of the present study, which can be only detected on the basis of much larger samples or by prospective studies.…”
Section: Discussionmentioning
confidence: 99%